Effect of sodium glycyrrhetinate on neonatal rat myocardial cells - Zhu Xiao-Wei; Meng Fu-Min (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of sodium glycyrrhetinate (SG) on neonatal rat myocardial cells. METHODS: The neonatal rat myocardial cells were cultured in vitro. Radioimmunoassay and fluorimetry were used to determine cAMP and [Ca2+], respectively. RESULTS: The beating rate of myocardial cells was depressed by SG 0.4 mmol.L-1 at 5, 10, and 15 min, from 73 +/- 9 min-1 to 62 +/- 5, 59 +/- 7, and 56 +/- 6 min-1, respectively. SG 0.1 and 0.2 mmol.L-1 showed above similar results at 15 min and 10, 15 min, respectively. When the myocardial cells were incubated with SG 0.2 and 0.4 mmol.L-1 at 37 degrees C for 10 and 15 min, the concentration of cAMP and- [Ca2+] were reduced. cAMP contents in SG 0.2 mmol.L-1 treated group at 10 and 15 min were lower than control group (1.09 +/- 0.18 vs 1.65 +/- 0.48 pmol per vial, P < 0.05; 1.12 +/- 0.35 vs 1.72 +/- 0.49 pmol per vial, P < 0.01), and so was [Ca2+] (30 +/- 4 nmol.L-1 vs 41 +/- 6 nmol.L-1, P < 0.05 and 28 +/- 6 nmol.L-1 vs 38 +/- 7 nmol.L-1, P < 0.01). SG 0.1 and 0.2 nmol.L-1 increased the pO2 change rate (87% +/- 5%, 75% +/- 4% vs 54% +/- 3%, P < 0.01) in suspension fluid of myocardial cells, but SG 0.4 mmol.L-1 decreased it (31% +/- 2% vs 54% +/- 3%, P < 0.01). CONCLUSION: SG protects myocardium or treats ischemic cardiac disease.